2010
DOI: 10.1021/jp103953w
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Computational Studies of the Laser Photolysis of Matrix Isolated 1,2-Dibromoethanes: Formation and Fate of the Bromoethyl Radicals

Abstract: We report experimental and computational studies of the photolysis of atmospherically important 1,2-dibromoethanes (1,2-C(2)X(4)Br(2); X = H, F) in Ar matrixes at 5 K. Using the pulsed deposition method, we find that significant conformational relaxation occurs for 1,2-C(2)H(4)Br(2) (EDB; observed anti/gauche ratio =30:1) but not for 1,2-C(2)F(4)Br(2) (TFEDB; anti/gauche = 3:1), which is traced to a larger barrier to rotation about the C-C bond in the latter. Laser photolysis of matrix-isolated EDB at 220 nm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…As we have shown in several previous studies of matrix isolated species, (12,15,28) the integrated IR and UV-Visible intensities can be combined with calculated IR intensities to estimate oscillator strengths of UV-Visible transitions. The integrated IR absorbance of a given feature was divided by the calculated intensity (in km/mol) to derive a column density in the matrix, and an average value was obtained over the observed IR absorptions (Table S1).…”
Section: Experimental and Computational Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…As we have shown in several previous studies of matrix isolated species, (12,15,28) the integrated IR and UV-Visible intensities can be combined with calculated IR intensities to estimate oscillator strengths of UV-Visible transitions. The integrated IR absorbance of a given feature was divided by the calculated intensity (in km/mol) to derive a column density in the matrix, and an average value was obtained over the observed IR absorptions (Table S1).…”
Section: Experimental and Computational Methodsmentioning
confidence: 96%
“…(9) We can reproduce this result, but find it is a by-product of spin contamination in the UMP2 wavefunction. For example, a fully relaxed scan of the C-C-I bond angle with the UM062x method, which performs well for the bromoethyl case, (12) shows a minimum corresponding to the bridged radical, but no other inflection point; i.e., the C-I bond distance increases with bond angle as the iodine atom is scanned off ( Figure S2). Stability tests of the UM062x wavefunction along this scan were performed which verified that the wavefunction contained no internal instabilities.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Kalume et al reported experimental and computational studies of the photolysis of atmospherically important 1,2-dibromoethanes of general formula 1,2-C 2 X 4 Br 2 (X = H, F) in Ar matrices at 5 K. 27 They found that a significant conformational relaxation occurs for 1,2-C 2 H 4 Br 2 (observed anti/gauche ratio = 30:1) but not for 1,2-C 2 F 4 Br 2 (anti/gauche = 3:1), which was explained taking into account the larger barrier to rotation about the C-C bond in the latter compound. It was suggested that the matrix pulsed deposition method, as compared with conventional continuous deposition methods, can lead to an increased conformational relaxation for systems with low barriers to internal rotation.…”
Section: Conformational Isomerizationsmentioning
confidence: 99%
“…In turn, Kalume et al 47 investigated bromoethyl radicals. These radicals were generated by 220 nm laser irradiation of a 1:500 1,2-C 2 H 4 Br 2 /Ar matrix, at 5 K. Irradiation in these conditions induced the formation of the gauche conformer of 1,2-dibromoethane and the C 2 H 4 -Br 2 charge transfer complex as major products, and the C 2 H 4 Br radical and the C 2 H 3 Br-HBr complex as minor products.…”
Section: Fragmentation Reactions and Formation Of Complexes Or Weaklymentioning
confidence: 99%
“…When these compounds transported and photolyzed in the stratosphere, can produce Br atoms that participate in ozone destruction cycle an important example of these compounds is bromopropane. Bromopropane has been used as the active component of industrial cleaning solvents where under UV-radiation undergoing photoreaction consists of excitation of nonbonding p electron of bromine directly to the lowest energy available antibonding molecular orbital followed by a quick dissociation, which involving n → σ* electronic excitation localized on the C-Br bond [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%